Percutaneous transhepatic venoplasty: an alternative treatment for Budd-Chiari syndrome - Kadir BAHAR; Selim KARAYALÇIN; Muhsin KAYA; Hülya ÇETİNKAYA and Hakan BOZKAYA and Cihan YURDAYDIN (Turkish Journal of Gastroenterology, 2019)
-